2008
DOI: 10.1080/13811110802101153
|View full text |Cite
|
Sign up to set email alerts
|

Consistency in Suicide Rates in Twenty-Two Developed Countries by Gender over Time 1874–78, 1974–76, and 1998–2000

Abstract: To determine whether the relative levels of suicide rates among the 22 developed countries were consistent over time 1974--76 v 2000--02 and to compare Durkheim's 11 European countries 1874--78 with their modern counterparts, including the 1984--86 period associated with the European recession. Data from the WHO of All Age "General Population Suicide Rates" (GPSR) by sex were calculated to obtain 3-year averages for the end-points. To determine the consistency of the levels of suicides a series of Spearman Ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…Another possibility is that there may be complex interaction between cultural, sociological and genetic factors. 27 A study of suicide rates in major European countries between 1874 to 2000 reported variation in suicide rates within the countries over time, but the relative rates between countries were consistent. 27 This suggested the possibility of interactions between genetic and other environmental factors and this requires further examination.…”
Section: Discussionmentioning
confidence: 99%
“…Another possibility is that there may be complex interaction between cultural, sociological and genetic factors. 27 A study of suicide rates in major European countries between 1874 to 2000 reported variation in suicide rates within the countries over time, but the relative rates between countries were consistent. 27 This suggested the possibility of interactions between genetic and other environmental factors and this requires further examination.…”
Section: Discussionmentioning
confidence: 99%
“…(WHO, 2005) These countries also have remarkable suicide rate trends from 1974/1976 to 1999/2000, in which rates for both countries exhibited increases in not only absolute values, but also rank among developed countries by three places. (Hansen and Pritchard, 2008) Highly refined comparisons are then required to determine risk-factors that shed light on these differences at the micro-level through the careful study of suicidal behaviours. This was possible using the European Study of the Epidemiology of Mental Disorders (ESEMeD), a part of the World Mental Health Surveys, which comprises of several population-based surveys including structured psychiatric interviews in six European countries, measuring, among others, the presence of mental disorders, suicidal behaviour, religious affiliation, social factors, use of case, and parental-bonding.…”
Section: Introductionmentioning
confidence: 99%
“…Rather, they are indicative of changes found in other studies of non-Western societies such as Islamic, Latin American and former Warsaw Pact countries related to suicide and child-abuse-related deaths, where data accuracy has been found to be problematic because of cultural and political taboos [15][16][17]. Nonetheless, despite these limitations, this first-ever comparative study of societies' response to children in three world regions provides significant indicators of those meriting a relative regional reproach or commendation.…”
Section: Discussionmentioning
confidence: 99%
“…There are inherent methodological problems with international comparisons of mortality but the following method has sought to minimise them, as utilised in a number of comparative international studies covering healthcare, suicide, child-abuse-related deaths, cancer and neurological disease [15][16][17][18]. Nonetheless, there can be limitations linked to the accuracy of mortality data in less industrialised nations [1,8,19].…”
Section: Methodsmentioning
confidence: 99%